The application of GIS based multi-criteria analysis for selecting an optimum water reservoir site - Bakhtyar Ali Ahmad, 1985- author; Mohd. Safie Mohd., supervisor; Fakulti Geoinformasi Dan Harta Tanah (2014)
Thesis (Sarjana Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2014